A virtuous cycle of co‐production: Reflections from a community priority‐setting exercise - Deborah Ikhile; Devyn Glass; Kat Frere‐Smith; Sam Fraser; Keith Turner; Hasu Ramji; Georgie Gremesty; Elizabeth Ford; Harm vanMarwijk (Wiley, 2023)
Abstract Introduction Co‐production is gaining increasing recognition as a good way of facilitating collaboration among different stakeholders, including members of the public. However, it remains an ambiguous concept as there is no definitive or universal model of co‐production or clarity on what constitutes a good co‐production approach. This paper draws on the reflections of the academic researchers, practitioners and public advisors involved in co‐producing a priority‐setting exercise. The exercise was conducted by the Primary and Community Health Services (PCHS) Theme of the National Institute for Health and Care Research Applied Research Collaboration for Kent, Surrey and Sussex (NIHR ARC KSS). Methods We collected data through written and verbal reflections from seven collaborators involved in the PCHS priority‐setting exercise. We used Gibbs' model of reflection to guide the data collection. We then analysed the data through an inductive, reflexive thematic analysis. Results A common thread through our reflections was the concept of 'sharing'. Although co‐production is inherently shared, we used the virtuous cycle to illustrate a sequence of sharing concepts during the research cycle, which provides the underpinnings of positive co‐production outcomes. We identified six themes to denote the iterative process of a shared approach within the virtuous cycle: shared values, shared understanding, shared power, shared responsibilities, shared ownership and positive outcomes. Conclusion Our results present a virtuous cycle of co‐production, which furthers the conceptual underpinnings of co‐production. Through our reflections, we propose that positive co‐production outcomes require foundations of shared values and a shared understanding of co‐production as a concept. These foundations facilitate a process of shared power, shared responsibilities and shared ownership. We argue that when these elements are present in a co‐production exercise, there is a greater potential for implementable outcomes in the communities in which the research serves and the empowerment of collaborators involved in the co‐production process. Public Members' Contributions Three members of the public who are public advisors in the NIHR ARC KSS were involved in the priority‐setting exercise that informed this paper. The public advisors were involved in the design of the priority‐setting exercise and supported participants' recruitment. They also co‐facilitated the focus groups during data collection and were involved in the data analysis, interpretation and preparation of the priority‐setting report. For this current manuscript, two of them are co‐authors. They provided reflections and contributed to the writing and reviewing of this manuscript.